VILLAGE-OWNED ENTERPRISES STRATEGYIN EMPOWERING LOCAL COMMUNITIES "BENDO VILLAGE, KAPAS DISTRICT, BOJONEGORO DISTRICT. - Hidayat, A. Taufiq; Fajar Surahman; Iki Yusran (⁠International Journal of Sustainable Social Culture, Science Technology, Management, and Law Humanities, 2024)
Hope of Village-Owned Enterprises applied by the grobogan reservoir tourism manager was able to empower local communities to be more productive whose output of the grobogan reservoir became a business entity owned by Bendo village which provided the largest village income outperforming the other Bendo village companies considering that other Bendo village businesses suffered losses like the rice barn Village-Owned Enterprises. The purpose of this study is to understand and describe: Strategies of Village-Owned Enterprises in Empowering Local Communities. Study of Grobogan Reservoir Tourism Management in Bendo Village, Kapas District, Bojonegoro Regency. The research method used is qualitative and the research subjects are informants who are clearly related to their duties and functions who can provide accurate and significant information relating to the strategy of the Grobogan Reservoir Village Owned Enterprise. Determination of the informants by means of purpose sampling. Based on the results of the study, the strategy used was SOS, meaning "Zinc is important for me". Starting from youth youth who are accustomed to meeting around the reservoir, then believe the reservoir can be turned into a tourist area, individual contribution capital without assistance from the village can attract visitors, the village finally provides assistance and is now a village-owned enterprise unit, the welfare of members of tourism organizations increases from 100 thousand / week to 300 thousand / week. The well-being of the local community came into being with various business stalls and stalls around the reservoir. The conclusion is that actions rationally based on clear goals and beliefs can arouse the spirit of making things happen, in this case empowering local communities through tourism development.